The Impact of the PQ4R Strategy on Reading Comprehension of Arabic Qur`anic Tafsir: A Study of Ninth-Grade Madrasah Students (Al-IRTIQA: Journal of Arabic Education and Linguistics, 2025)
This study aims to examine the impact of the PQ4R strategy (Preview, Question, Read, Reflect, Recite, Review) in enhancing the comprehension of Arabic Qur`anic Tafsir texts among ninth-grade students of Madrasah Tsanawiyah Pesantren Modern Darul Qiyam, Kerinci Regency. The research employed a quasi-experimental one group pretest-posttest design involving 17 students (11 females and 6 males) in the 2023/2024 academic year. Data were collected using multiple-choice reading comprehension test consisting of 25 items covering five aspects: main ideas, supporting details, reference, inference, and vocabulary. The data were analyzed using paired-sampel t-test with SPSS 26.0. The results revealed a significant improvement in reading comprehension scores after implementing the PQ4R strategy. The mean pre-test score was 64,12 which increased to 78,47 in the post-test. The paired t-test indicated t-value = 5,62 > t-tabel = 2,12 at at the 0,05 significance level (p < 0,05), confirming the acceptance on the alternative hypothesis. Therefore, the PQ4R strategy proved effective in improving students` comprehension of Arabic Tafsir Texts across cognitive, metacognitive, and affective dimensions, while also fostering reflective and independent learning attitudes.